Pengaruh Lingkungan Kerja Fisik, Disiplin Kerja, dan Komunikasi terhadap Kinerja Pegawai DPMD Kabupaten Lumajang - Puspita, Leonita Dwi; Susanto, Arnis Budi; Prajitiasari, Ema Desia; Saleh, Chairul; Priyanto, Fajar Wahyu; Titisari, Purnamie; Wiryaningtyas, Dwi Perwitasari; Susetyarsi, Theresia (Study Program of Management Faculty of Economics and Business University of Jember, 2024)
Abstract This research aims to analyze the influence of the physical work environment, work discipline and communication on employee performance at the Lumajang Regency Community and Village Empowerment Service. This research uses quantitative methods with survey methods and data collection carried out through questionnaires to employees of the Community and Village Empowerment Service. The number of employees sampled for this research was 55 people. The results of data analysis using multiple linear regression show that the physical work environment has a significant positive influence on employee performance. Work discipline also has a positive and significant influence on employee performance. Apart from that, communication has also been proven to have a positive and significant effect on employee performance.